STUDI PROSES MELUKIS WAYANG KAMASAN DI SANGGAR LUKIS KLASIK KAMASAN WASUNDARI KAMASAN, KLUNGKUNG, BALI - Putra Astawa, I Gede; Berata, I Made; Mertanadi, I Made (Pusat Penerbitan LPPM ISI Bali, 2025)
The art of Kamasan puppet painting is a great tradition that deserves attention from the condition of its existence which is experiencing a decline in the next generation of its continuity. This phenomenon is the impact of the skyrocketing modern technology that colonizes the world in seconds. The emergence of digital technology that offers convenience and instant affects the mindset of the young generation of Kamasan Village, eliminating the traditional art of wayang kamasan that is able to sweep its era. This phenomenon is very interesting to explore more closely through the Merdeka Belajar Kampus Merdeka (MBKM) program implemented directly in the field, with the aim of absorbing the process of painting wayang kamasan. Data collection and data analysis use qualitative methods, where researchers are involved in the daily activities of the artists at the Wasundari Wayang Kamasan classical painting studio. In the implementation of the process of painting wayang kamasan, the threestage method and steps of the art creation process are applied to discuss the issues raised, namely the process of painting wayang kamasan through a hierarchical perspective born from the concept of Tri Loka, understanding the figures and characters of wayang, the substance of the literary text that is the source of creation, and understanding the concept of how to read the visual narrative of wayang kamasan painting. The organization of puppet figures or characters that function as “text” in visual language, which can represent the substance of the “context” of the literary text illustrated in the form of puppet paintings. This stage of the painting process is considered complicated and time-consuming, not worth the work with the final result.